A Delphi developed syllabus for the medical specialty of sport and exercise medicine. Issue 8 (20th December 2017) - Humphries, David; Jaques, Rod; Dijkstra, Hendrik Paulus
Abstract : Training in the medical specialty of sport and exercise medicine is now available in many, but not all countries. Lack of resources may be a barrier to the development of this important specialty field and the International Syllabus in Sport and Exercise Medicine Group was convened to reduce one potential barrier, the need to develop a syllabus. The group is composed of 17 sport and exercise medicine specialists residing in 12 countries (Australia, Canada, India, Ireland, Malaysia, the Netherlands, Qatar, South Africa, Sweden, Switzerland, the UK and USA). This paper presents the first phase of this project covering the domains and general learning areas of a specialist training syllabus in sport and exercise medicine.